2015
DOI: 10.1111/petr.12483
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of acute kidney injury in pediatric allogeneic hematopoietic stem cell recipients

Abstract: The process of allogeneic HSCT in children is associated with frequent AKI and mortality, but the epidemiology is not widely reported. The aim of this review was to summarize the available evidence on incidence, risk factors, timing, and prognosis of AKI in children following HSCT. We systematically reviewed all observational studies reporting incidence and outcomes of AKI in pediatric allogenic HSCT recipients. The minimum criteria for AKI were defined as an increase in sCr ≥ x1.5 or urine output ≤0.5 mL/kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
1
30
0
1
Order By: Relevance
“…Recently, Ileri et al 21 published a prospective study of 61 pediatric myeloablative and allogenic HSCT recipients and reported the incidence of AKI to be 42% within the first 100 days posttransplant. A recent systemic review of AKI in pediatric HSCT recipients included five observational studies and concluded that one-third of pediatric HSCT recipients developed AKI 10 . The cited studies used doubling of serum creatinine as their criterion for diagnosis of AKI except for Ileri et al The incidence of AKI in these studies is substantially lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ileri et al 21 published a prospective study of 61 pediatric myeloablative and allogenic HSCT recipients and reported the incidence of AKI to be 42% within the first 100 days posttransplant. A recent systemic review of AKI in pediatric HSCT recipients included five observational studies and concluded that one-third of pediatric HSCT recipients developed AKI 10 . The cited studies used doubling of serum creatinine as their criterion for diagnosis of AKI except for Ileri et al The incidence of AKI in these studies is substantially lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric data have identified sepsis, VOD, TBI, non-HLA-identical related or matched unrelated donors and nephrotoxicity associated with cyclosporine, amphotericin B and forscarnet as risk factors 20, 21, 27 . Although adult studies have elucidated myeloablative conditioning 28 , female sex, high-risk disease and aGVHD 29 as risk factors for AKI, pediatric data have not replicated these findings 10 . This may be because pediatric studies are smaller and underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] More than 50% of patients with childhood AML will require an allogeneic HSCT to consolidate high-risk disease or to salvage relapse disease. HSCT is a known high-risk period for children and adults to develop AKI, [43][44][45][46][47][48][49] as recently confirmed by the University of Minnesota 50 where 174 of 205 children and adolescents (84%) developed AKI during the first year following a first HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is critical to avoid exacerbating AKI with aggressive diuresis or rapid removal of ascetic fluid. HCT recipients often require intravenous parenteral nutrition, frequent administration of blood products, and multiple nephrotoxic medications, all of which may worsen FO, further contributing to AKI . Therefore, management of AKI and FO in HCT patients is particularly challenging; and when FO >20% or is refractory to conventional pharmaceutical diuresis, CRRT may need to be considered.…”
Section: Discussionmentioning
confidence: 99%